THE EFFECT OF RETURN ON ASSET AND CURRENT RATIO ON DIVIDEND PAYOUT RATIO WITH FIRM SIZE AS A MODERATING VARIABLE IN CONSTRUCTION AND BUILDING SUB-SECTOR SERVICE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Farina Jessen Yap; Elidawati; Pius Deski Manalu (Journal of Financial Management & Accounting, 2025)
The rise of investment in the present has become the interest of the people of Indonesia. The number of Indonesian capital market investors reached 1.9 million while for stock investors it had reached 952,000. This shows that there is high interest of the Indonesian people in saving and investing in shares. This study aims to determine whether there is an influence of financial ratios that will be examined against the Dividend Payout Ratio. The population in this study were 17 companies with a main sample of 8 companies and the length of the study was 4 years. The data analysis technique used is Moderated Regression Analysis because there is a moderating variable in this study. The results showed that Return On Assets had a significant and negative effect on Dividend Payout Ratio. Current Ratio does not affect the Dividend Payout Ratio. There is a simultaneous effect between Return On Assets and Current Ratio on Dividend Payout Ratio. Firm Size which is a moderating variable can only act as an independent variable. Keywords: Return On Assets, Current Ratio, Dividend Payout Ratio, Firm Size